2008
DOI: 10.1128/aem.02687-07
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mineralization of the Phenylurea Herbicide Diuron by Variovorax sp. Strain SRS16 in Pure Culture and within a Two-Member Consortium

Abstract: The phenylurea herbicide diuron [N-(3,4-dichlorophenyl)-N,N-dimethylurea] is widely used in a broad range of herbicide formulations, and consequently, it is frequently detected as a major water contaminant in areas where there is extensive use. We constructed a linuron [N-(3,4-dichlorophenyl)-N-methoxy-N-methylurea]-and diuron-mineralizing two-member consortium by combining the cooperative degradation capacities of the diuron-degrading organism Arthrobacter globiformis strain D47 and the linuron-mineralizing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 53 publications
5
98
1
1
Order By: Relevance
“…The strain was named Variovorax strain VC1. Variovorax species display multiple metabolic features including the biotransformation of the herbicides linuron 13 and diuron 14 and of synthetic (2,4-dinitrotoluene) and naturally occurring (3-nitrotyrosine) nitroaromatic compounds. 15,16 Growth of VC1 with NQ as the sole nitrogen source in the presence of 10 mM glucose is presented in Figure 2a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The strain was named Variovorax strain VC1. Variovorax species display multiple metabolic features including the biotransformation of the herbicides linuron 13 and diuron 14 and of synthetic (2,4-dinitrotoluene) and naturally occurring (3-nitrotyrosine) nitroaromatic compounds. 15,16 Growth of VC1 with NQ as the sole nitrogen source in the presence of 10 mM glucose is presented in Figure 2a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Joshi et al (2008) reported acid orange decolorization was significantly higher with the use of consortium as compared to the use of individual strains. Bacterial cocultures have been used to increase the rate of degradation of phenol (Jiang et al 2006) and diuron (Sørensen et al 2008 …”
Section: Discussionmentioning
confidence: 99%
“…Dutta et al [48] described that root colonization and promotion of growth can be affected due to root exudates prompting alterations in the cell surface of B. cereus. Dead microbial structures can possibly work as nutrient source for the growth of strains in the co-culture [49].…”
Section: Growth Of Sde 2-40 B Cereus and Co-culture On Agarose Andmentioning
confidence: 99%